Distance to health services modifies the effect of an 11-valent pneumococcal vaccine on pneumonia risk among children less than 2 years of age in Bohol, Philippines. (6th September 2016) - Root, Elisabeth Dowling; Lucero, Marilla; Nohynek, Hanna; Stubbs, Rebecca; Tallo, Veronica; Lupisan, Socorro P; Sanvictores, Diozele M; Nillos, Leilani T; Simões, Eric AF; ,
Abstract: Background: Both vaccine trials and surveillance studies typically use passive surveillance systems to monitor study outcomes, which may lead to under-reporting of study outcomes in areas with poor access to care. This detection bias can have an adverse effect on conventional estimates of pneumonia risk derived from vaccine trials. Methods: We conducted a secondary analysis of a randomized, placebo-controlled, double-blind vaccine trial that examined the efficacy of an 11-valent pneumococcal vaccine (PCV) among children less than 2 years of age in Bohol, Philippines. Trial data were linked to the residential location of each participant using a geographical information system. The study was conducted using 11 729 children who received three doses of any study vaccine (PCV11) or placebo. Multivariate Cox proportional hazards models were used to examine major risk factors for pneumonia diagnosis and the relationship between distance to Bohol Regional Hospital (BRH) and vaccination with PCV with risk for pneumonia diagnosis. Results: There was a significant interaction effect between distance from BRH and vaccination with PCV11 on pneumonia risk. Among children living 12 km from BRH, vaccination with PCV11 was associated with a decreased hazard ratio for radiographic pneumonia, compared with vaccination with the study placebo [0.57, 95% confidence interval (CI) 0.37–0.86). However, for children living 1 km from BRH, there was little difference in risk of radiographic pneumonia diagnosis between children vaccinated with PCV11 and those given the study placebo. Conclusion: Children living close to BRH had no documented reduction in the primary study outcome from PCV11, whereas those at greater distance experienced a substantial reduction. Because of detection bias caused by distance to BRH, in spatial analysis of vaccine trial results it may be necessary to adjust estimates of pneumonia risk and vaccine efficacy. Failure to consider the geographical dimension of trials may lead to underestimates of efficacy which might influence public health planning efforts.